Genomic DNA Insertions and Deletions Occur Frequently Between Humans and Nonhuman Primates - Frazer, Kelly A.; Chen, Xiyin; Hinds, David A.; Pant, P.V. Krishna; Patil, Nila; Cox, David R. (Genome Research, 2003)
Comparative DNA sequence studies between humans and nonhuman primates will be important for understanding the genetic basis of the phenotypic differences between these species. Here we compare ∼27 Mb of human chromosome 21 with chimpanzee DNA sequences identifying 57 genomic rearrangements (deletions and insertions ranging in size from 0.2 to 8.0 kb) between the two species. These rearrangements are distributed along the entire length of chromosome 21, with ∼35% found in genomic intervals encoding genes (genic intervals), and have occurred in the genomes of both humans and chimpanzees. Comparison of ∼9 Mb of human chromosome 21 with orangutan, rhesus macaque, and woolly monkey DNA sequences identified a combined total of 114 genomic rearrangements between humans and nonhuman primates. Analysis of these rearrangements revealed that they are randomly distributed with respect to genic and nongenic intervals and identified one deletion that has likely resulted in the inactivation of a gene (β1,3-galactosyltransferase) in the woolly monkey. Our data show that genomic rearrangements have occurred frequently during primate genome evolution and significantly contribute to the DNA differences between these species. These DNA rearrangements are commonly found in genic intervals, and thus provide natural starting points for focused investigations of qualitative and quantitative gene expression differences between humans and other primates.[Supplemental material is available online atwww.genome.org.]